A novel staging system for caries severity in the primary dentition. (16th June 2016) - Robertson, Lawrence D.; Beltrán‐Aguilar, Eugenio; Dasanayake, Ananda; Phipps, Kathy R.; Warren, John J.; Hennessy, Thomas W.
Abstract: Objectives: Caries in the primary dentition (CIPD) has a high prevalence in U.S. children compared to other diseases, with substantial disparities among different population groups. Few reports correlate CIPD prevalence with clinical impairment of children's quality of life, such as tooth pain, speech delay or trauma to the child from operative restorations, which we collectively term morbidity . Likewise, current case definitions (ECC, S‐ECC) and disease metrics (mean dmfs/dmft) are not helpful in assessing morbidity for individual or groups of children. We describe a construct to stage caries severity for children ages 0 ‐5, called "CIPD Levels." This metric is based on small interval age‐group dmft scores, and has a direct link to current and predicted morbidity for the child. It is modeled after staging systems for medical diseases in which the various stages or levels are correlated with the probability of morbidity or mortality. Methods: We created a matrix in which CIPD Levels 0–4 are assigned for dmft scores 0‐7 depending on a child's age. CIPD Level‐4 is the highest level, and frequently results in clinical adverse outcomes, including pain and extensive restorations. We next tested this matrix with data from a high‐risk population. Results: Among children with any cavitated caries at age <24 months, 82.8% reached the adverse outcomes threshold (CIPD Level‐4) at age 36 months. For children with dmft = 0 at 24 months, 71.4% did not reach CIPD Level‐4 at age 36 months. Conclusion: Our new metric is useful for quantifying disease burden from caries for high‐risk children.